Management of the ground force reserve components in development of defense posture to face threats in West Kalimantan Province - Edy Saptono; Supriyatno, Makmur; Widodo Putro, Resmanto; Kristijarso (Technium Social Sciences Journal, 2022)
West Kalimantan Province geographically is part of Indonesia which borders directly with neighboring countries with potential hybrid threats and non-military threats. Based on the Law of the Republic of Indonesia Number 3 of 2002 concerning National Defense explained that the defense of Indonesia organized with a universal defense system to face any form of threat. Indonesian defense posture relying on the Indonesian National Army as the main component who are ready to face the threat. In accordance with the mandate of the Republic of Indonesia Law Number 23 of 2019 concerning Management of National Resources, in addition to relying on the strength and capabilities of the Indonesian National Army, also involves reserve components who have received basic military training to increase the strength of the main components in a short time. This study aims to analyze the management, constraints and efforts made in management of the ground force reserve component in the development of a defense posture to deal with threats in West Kalimantan Province. The method used in this research is qualitative method with primary data collection techniques that is interviews with resource persons and secondary data in the form of literature studies. Results research shows that management of the ground force reserve component implemented by territorial command through the management functions of planning, organizing, actuating and controlling. The obstacles faced are geographical factors, budget constraints, central and local governments and companies do not understand the regulations, limited educators, trainers and infrastructure, limited communication tools to control the members of the ground force reserve component. As for efforts to overcome obstacles in management of the ground force reserve component in West Kalimantan Province is to optimize the implementation of socialization, intensify budget coordination, increase the quantity and quality of human resources and improve facilities and coaching programs.